Identification of Colibacillosis and Antibiotic Resistance Test in Free-range Chicken: Identifikasi Kolibasilosis dan Uji Resistensi Antibiotik pada Ayam Kampung - Wulandari, Eka; Amri, Indah Amalia (Faculty of Veterinary Medicine Universitas Brawijaya, 2022)
Escherichia coli are normal flora in the digestive tract of animals and humans but can be opportunistic under certain conditions. Apart from normal flora, there are also pathogenic strains of the E. coli bacteria that can cause disease in the hospes. The disease that can be caused by E. coli bacteria is colibacillosis which often occurs in poultry. One of the clinical symptoms that appear in chickens suffering from colibasillosis is diarrhea which can arise due to enteritis. This study aims to identify the incidence of colibacillosis and antibiotic resistance of E. coli bacteria in Free-range Chicken. Clinical symptoms showed that the animal looked weak, had diarrhea, and had feces around the cloaca. The necropsy results showed the presence of hemorrhage in the duodenum and caecum. Samples of organ swabs that experienced hemorrhage were then tested for isolation and identification of E.coli bacteria and antibiotic resistance using the Kirby-Bauer method for five types of antibiotics, penicillin, bacitracin, gentamicin, cefadroxil, and ciprofloxacin. The test results showed that the Free-range Chicken had colibacillosis. The E. coli bacteria that cause colibacillosis were resistant to penicillin and bacitracin antibiotics, intermediates to cefadroxil, and sensitive to ciprofloxacin and gentamicin.